2018
DOI: 10.1111/tri.13336
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between socioeconomic deprivation and likelihood of pre-emptive transplantation: influence of competing risks and referral characteristics - a retrospective study

Abstract: Socioeconomic deprivation (SED) influences likelihood of pre-emptive kidney transplantation (PET), but the mechanisms behind this are unclear. We explored the relationships between SED and patient characteristics at referral, which might explain this discrepancy. A retrospective cohort study was performed. SED was measured by Scottish Index of Multiple Deprivation (SIMD). Logistic regression evaluated predictors of PET. A competing risks survival analysis evaluated the interaction between SED and progression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…22 We also found that people of lower SES are more likely to have CKD after age and sex adjustment. This is an important finding given that individuals of lower SES have greater mortality due to comorbid factors which then predict mortality on an independent basis, 23 including obesity and associated cardiovascular risk factors. 17 Adjusting for age, sex, and deprivation reversed the direction of association for PD and dementia so both had odds-ratios <1.…”
Section: Discussionmentioning
confidence: 87%
“…22 We also found that people of lower SES are more likely to have CKD after age and sex adjustment. This is an important finding given that individuals of lower SES have greater mortality due to comorbid factors which then predict mortality on an independent basis, 23 including obesity and associated cardiovascular risk factors. 17 Adjusting for age, sex, and deprivation reversed the direction of association for PD and dementia so both had odds-ratios <1.…”
Section: Discussionmentioning
confidence: 87%
“…While living donor kidney transplantation (LDKT) is the best treatment option with chronic kidney disease (CKD) in terms of survival and quality of life [ 1 , 2 ], research has shown that there is inequality in access to LDKT [ 3 , 4 ]. A number of modifiable factors, such as patients’ knowledge on kidney replacement therapy (KRT), communication with family and friends about KRT, and cultural sensitivity of health care professionals are independently related to the access to LDKT [ 5 , 6 ]. A home‐based educational intervention has been developed to address these factors.…”
Section: Introductionmentioning
confidence: 99%
“…(4) While living-donor transplantations became more common among Jewish children, Arab and Druze children did not demonstrate this trend, resulting in a prolonged absolute waiting time for kidney transplantation. (5) We observed a poorer prognosis among infants on dialysis, although their prognosis improved significantly over the study period. We also observed poorer prognosis among minority groups.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies demonstrated specifically the adverse effect of low socioeconomic status and immigration on the likelihood to undergo living-donor kidney transplantation. 47…”
Section: Introductionmentioning
confidence: 99%